The Construction of the Lust Measurement Instrument According to Al-Ghazali - Nurkholis Madani Daud; Wahyu Jati Anggoro (Universitas Muhammadiyah Surakarta, 2025)
This study aims to create an instrument for measuring lust and validate the construct of lust measurement according to Al-Ghazali. In broad line, this research was carried out in two stages, namely (1) construction of a measuring instrument for nafs, and (2) field trials and evaluation of psychometric properties. The first stage produces 42 items that have been justified by 14 Subject Matter Experts (SME). In the second stage, by using confirmatory factor analysis (CFA) evaluation and through comparison of unidimensional and multidimensional models as well as through concurrent validity with a self-control scale based on data from 319 participants, a valid multidimensional model of lust measurement instrument was obtained and formed the dimensions of syahwat state, anger state, and spiritual reasoning. There are 13 valid items with a Likert model response 1-5 (Strongly Disagree - Strongly Agree). The results of the reliability estimation indicate that the lust measurement instrument has good consistency. Based on the results of additional analysis, namely the correlation with the Big Five personality traits, it also shows that personality traits have a relationship with individual lust.